Low frequency wireless power transfer using modified parallel resonance matching at a complex load - Artit Rittiplang (KKU Engineering Journal, 2016)
In the Impedance Matching (IM) condition of Wireless Power Transfer (WPT), series resonant and strong coupling structures have been widely studied which operate at an optimal parameter, a resistive load, and the high resonant frequency of greater than 1 MHz. However, i) The optimal parameter (particular value) limits the design, ii) the common loads are complex, iii) The high frequency RF sources are usually inefficient. This paper presents a modified parallel resonant structure that can operate at a low frequency of 15 kHz without an optimal parameter under the IM condition with a complex load, and the calculated efficiency is equal to 71.2 % at 5-cm transfer distance.